Symposium 1: Web 2.0 and the Net Generation - A Critical Perspective: Symposium Introduction - Ryberg, Thomas (Proceedings of the International Conference on Networked Learning, 2012)
In the recent years, social media and web 2.0 have been hot topics within educational debates and within the research area of networked learning. The latter is evident from symposia and papers from the last years' networked learning conferences, but also European research projects, special issues, and books have revolved around social media, web 2.0, personal learning environments, student-centred learning, and student-generated content. Alongside these internet developments we have witnessed debates on what schools and universities can do to cater to the 'net-generation' or the 'digital natives' in, or coming to, our educational institutions. Bennett et al. (2008) have likened some of the vocal calls for immediate educational change as 'academic moral panics' based on unsubstantiated speculations about a coming generation of digital natives with unprecedented high digital literacy. More and more evidence seems to suggest that the young people, who actually seem to fit the category of digital natives are a minority or elite, rather than a widespread phenomenon within an entire generation (Brown & Czerniewicz, 2010; Kennedy, Judd, Dalgarno, & Waycott, 2010). At the same time it is becoming increasingly clear that the use of web 2.0 technologies among young people is not as widespread or advanced as assumed. The use is more often for mundane purposes and entertainment, which runs counter to the envisioned or imagined educational ideals of using web 2.0 technologies for scholarly knowledge creation and sharing (Clark, Logan, Luckin, Mee, & Oliver, 2009; Selwyn, 2009) These are also issues we wish to address and contribute to in this symposium. The symposium consists of three papers, which all draw on data collected among students in Aalborg University (AAU), Denmark. AAU is characterised by its problem and project based pedagogy (called the Aalborg PBL model). The main pedagogical principles within the PBL model of AAU is organised around problem-orientation, project work, inter-disciplinarily, and participant controlled learning. The pedagogy is based on students’ enquiry into scientific and social problems as part of their learning process. In AAU, each semester is therefore organized around approximately 50% course work and 50% project work in groups, where students collaborate on writing their semester project. The students work closely together for an extended period of time (app. 4 months) on producing a project report reflecting the work with their self-chosen problem.